Permeation Properties of a P2X Receptor in the Green Algae Ostreococcus tauri - Fountain, Samuel J. (American Society for Biochemistry and Molecular Biology, 2008)
We have cloned a P2X receptor (OtP2X) from the green algae Ostreococcus tauri. The 42-kDa receptor shares ∼28% identity with human P2X receptors and 23% with the Dictyostelium P2X receptor. ATP application evoked flickery single channel openings in outside-out membrane patches from human embryonic kidney 293 cells expressing OtP2X. Whole-cell recordings showed concentration-dependent cation currents reversing close to zero mV; ATP gave a half-maximal current at 250 μm. αβ-Methylene-ATP evoked only small currents in comparison to ATP (EC(50) > 5 mm). 2′,3′-O-(4-Benzoylbenzoyl)-ATP, βγ-imido-ATP, ADP, and several other nucleotide triphosphates did not activate any current. The currents evoked by 300 μm ATP were not inhibited by 100 μm suramin, pyridoxal-phosphate-6-azophenyl-2′,4′-disulfonic acid, 2′,3′-O-(2,4,6-trinitrophenol)-ATP, or copper. Ion substitution experiments indicated permeabilities relative to sodium with the rank order calcium >choline >Tris >tetraethylammonium >N-methyl-d-glucosamine. However, OtP2X had a low relative calcium permeability (P(Ca)/P(Na) = 0.4) in comparison with other P2X receptors. This was due at least in part to the presence of an asparagine residue (Asn(353)) at a position in the second transmembrane domain in place of the aspartate that is completely conserved in all other P2X receptor subunits, because replacement of Asn(353) with aspartate increased calcium permeability by ∼50%. The results indicate that the ability of ATP to gate cation permeation across membranes exists in cells that diverged in evolutionary terms from animals about 1 billion years ago.